Glucose transporter-1 deficiency syndrome: the expanding clinical and genetic spectrum of a treatable disorder - Leen, Wilhelmina; Klepper, Joerg; Verbeek, Marcel M.; Leferink, Maike; Hofste, Tom; van Engelen, Baziel G.; Wevers, Ron A.; Arthur, Todd; Bahi-Buisson, Nadia; Ballhausen, Diana; Bekhof, Jolita; van Bogaert, Patrick; et al. (Brain, 2010)
Glucose transporter-1 deficiency syndrome is caused by mutations in the SLC2A1 gene in the majority of patients and results in impaired glucose transport into the brain. From 2004-2008, 132 requests for mutational analysis of the SLC2A1 gene were studied by automated Sanger sequencing and multiplex ligation-dependent probe amplification. Mutations in the SLC2A1 gene were detected in 54 patients (41%) and subsequently in three clinically affected family members. In these 57 patients we identified 49 different mutations, including six multiple exon deletions, six known mutations and 37 novel mutations (13 missense, five nonsense, 13 frame shift, four splice site and two translation initiation mutations). Clinical data were retrospectively collected from referring physicians by means of a questionnaire. Three different phenotypes were recognized: (i) the classical phenotype (84%), subdivided into early-onset (<2 years) (65%) and late-onset (18%); (ii) a non-classical phenotype, with mental retardation and movement disorder, without epilepsy (15%); and (iii) one adult case of glucose transporter-1 deficiency syndrome with minimal symptoms. Recognizing glucose transporter-1 deficiency syndrome is important, since a ketogenic diet was effective in most of the patients with epilepsy (86%) and also reduced movement disorders in 48% of the patients with a classical phenotype and 71% of the patients with a non-classical phenotype. The average delay in diagnosing classical glucose transporter-1 deficiency syndrome was 6.6 years (range 1 month-16 years). Cerebrospinal fluid glucose was below 2.5 mmol/l (range 0.9-2.4 mmol/l) in all patients and cerebrospinal fluid : blood glucose ratio was below 0.50 in all but one patient (range 0.19-0.52). Cerebrospinal fluid lactate was low to normal in all patients. Our relatively large series of 57 patients with glucose transporter-1 deficiency syndrome allowed us to identify correlations between genotype, phenotype and biochemical data. Type of mutation was related to the severity of mental retardation and the presence of complex movement disorders. Cerebrospinal fluid : blood glucose ratio was related to type of mutation and phenotype. In conclusion, a substantial number of the patients with glucose transporter-1 deficiency syndrome do not have epilepsy. Our study demonstrates that a lumbar puncture provides the diagnostic clue to glucose transporter-1 deficiency syndrome and can thereby dramatically reduce diagnostic delay to allow early start of the ketogenic diet.
Gesehen am 10.03.2023